Editors's Introduction to the Special Issue on "Advances in Semantic Information Retrieval" - Klyuev, Vitaly; Mozgovoy, Maxim (Informatica, 2014)
Editors's Introduction to the Special Issue on "Advances in Semantic Information Retrieval"